Editors' Choice—Solar-Electrochemical Platforms for Sodium Hypochlorite Generation in Developing Countries. Issue 12 (1st January 2019) - Chinello, Enrico; H. Hashemi, S. Mohammad; Psaltis, Demetri; Moser, Christophe
Abstract : On-site generation of sodium hypochlorite (NaClO) holds the potential to bring an efficient and cost-effective water disinfection method to isolated and remote locations. Solar-driven, stand-alone reactors could provide those communities full independence by ensuring continuous treatment of drinking water. In this study we build and compare the performance of two different classes of electrolyzers for sodium hypochlorite generation: the first one is flow-based, mimicking those commercially employed at large scale; the second class is batch-type, exemplifying a cheaper, simpler and more robust alternative, more suitable for developing countries. The performance of such devices has been assessed and it has been observed that the batch-type reactor suffers from lower current yields due to the loss of oxidized products. Nevertheless, the mechanism can be compensated by introducing structures (i.e. through holes) in the electrode plate. This has been validated experimentally and computationally. The efficiency and cost-effectiveness of solar-driven hypochlorite reactors have been assessed. Our study reveals that tailored solar modules are essential to ensure high conversion efficiencies and the cost competitiveness of the hypochlorite generated. Flow-based devices recorded superior performance and need smaller electrode areas to be powered; nevertheless, they are less suitable for deployment in remote and isolate locations due to reliability issues, and hurdles in components replacement. Batch-type devices are likely more amenable for such contexts, despite they require roughly 13 times larger electrodes, leading to hypochlorite production costs 6 times higher. Our study is the first thorough investigation of sodium hypochlorite generators specifically designed for deployment in developing countries, and could foster further research and engineering efforts in the domain of water disinfection in developing countries.